The Impact of Animated Pedagogical Agents on Girls' and Boys' Emotions, Attitudes, Behaviors and Learning - Arroyo, I.; Woolf, B. P.; Cooper, D. G.; Burleson, W.; Muldner, K. (2011 IEEE 11th International Conference on Advanced Learning Technologies, 2011)
We report on the reactions of males and female students to the presence of animated pedagogical agents that provided emotional and motivational support. One hundred high school students used agents embedded in an Intelligent Tutoring System for Mathematics and randomized controlled evaluations compared students with and without learning companions. The results indicate that affective pedagogical agents improve affective outcomes of students in general and particularly so for female students, who reported being more frustrated and less confident while solving math problems prior to using the tutoring system. We discuss issues of incorporating gender into user models and of generating responses tailored to gender.